3D CT‐Guided Pulsed Radiofrequency Treatment for Trigeminal Neuralgia. Issue 1 (21st February 2013) - Fang, Luo; Ying, Shen; Tao, Wang; Lan, Meng; Xiaotong, Yu; Nan, Ji
Abstract Trigeminal neuralgia (TN) is a pain syndrome characterized by pain in the trigeminal area often accompanied by a brief facial spasm or tic. The purpose of our study was to investigate the efficacy and clinical utility of CT‐guided pulsed radiofrequency (PRF) for treatment of TN. Patients who were diagnosed with severe TN between September 2010 and October 2010 at Beijing Tiantan Hospital were included. Pulsed radiofrequency treatment (PRFT) was employed to treat TN. To verify the accurate needle position, a thin‐section cranial CT scan was performed by using a multidetector CT scanner. Three‐dimensional reconstruction was performed to visualize the location of the needle and the foramen ovale. A total of 20 patients were included in the study. Seven patients (35%) had favorable outcome 1 year after the PRFT. The numeric rating scale in the 7 patients with good outcome was significantly lower than the 13 patients with bad outcome at 1 day, 1 week, and 2 weeks after the treatment. The remaining 13 patients had residual pain 2 weeks after the PRFT and had to receive radiofrequency thermocoagulation (RFTC). In conclusion, the results of our study demonstrate that CT‐guided PRFT is not an effective method of pain treatment for idiopathic TN as compared with conventional RFTC. However, CT‐guided PRFT is associated with less complication than RFTC.